PENGEMBANGAN BAHAN AJAR E-MODUL INTERAKTIF BERBASIS FLIP PDF CORPORATE EDITION UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH KONSTRUKSI BUSANA WANITA DI JURUSAN PKK FT UNM - Nur Wahdaniah; St. Aisyah; Nahriana (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2023)
This research aims to; (1) find out the results of developing interactive e-module teaching materials based on Flip PDF Corporate Edition in women's fashion construction courses to improve student learning outcomes in the PKK FT UNM Department; (2) produce e-module teaching materials based on Flip PDF Corporate Edition which are valid to be used as teaching materials in women's fashion construction courses in the PKK FT UNM Department; (3) produce e-module teaching materials based on Flip PDF Corporate Edition which are practically used as teaching materials in women's fashion construction courses in the PKK FT UNM Department; (4) produce e-module teaching materials based on Flip PDF Corporate Edition that effectively improve learning outcomes in women's clothing construction courses in the PKK FT UNM Department. This research method is research and development (Research and Development) with the ADDIE development model. The research subjects were 30 students and 1 lecturer of the PKK FT UNM Department. Data collection through interviews, observation, documentation and questionnaires were analyzed using quantitative descriptive statistical techniques. The results showed that: (1) The results of developing interactive e-module teaching materials based on Flip PDF Corporate Edition in women's fashion construction courses to improve student learning outcomes in the PKK FT UNM Department through the stages of Analysis, Design, Development (Development), Implementation (Implementation) and Evaluation (Evaluation). (2) Valid e-modules are used based on the value of media experts of 89.58 in the Very Valid category and material experts of 88.65 in the Very Valid category; (3) The practical e-module is used with a value from the lecturer of 95 in the Very Practical category, students of 94.31 in the Very Practical category, and observers of 94.44 in the Very Practical category, and (4) The N-Gain value of Pre -test and post-test were 0.80 in the High category so that it can be said that corporate flip pdf-based e-modules are effective in improving student learning outcomes in the course of women's clothing construction in the PKK FT UNM major.